SMN - A chaperone for nuclear RNP social occasions?. Issue 6 (3rd June 2017) - Raimer, Amanda C.; Gray, Kelsey M.; Matera, A. Gregory
ABSTRACT: Survival Motor Neuron (SMN) protein localizes to both the nucleus and the cytoplasm. Cytoplasmic SMN is diffusely localized in large oligomeric complexes with core member proteins, called Gemins. Biochemical and cell biological studies have demonstrated that the SMN complex is required for the cytoplasmic assembly and nuclear transport of Sm-class ribonucleoproteins (RNPs). Nuclear SMN accumulates with spliceosomal small nuclear (sn)RNPs in Cajal bodies, sub-domains involved in multiple facets of snRNP maturation. Thus, the SMN complex forms stable associations with both nuclear and cytoplasmic snRNPs, and plays a critical role in their biogenesis. In this review, we focus on potential functions of the nuclear SMN complex, with particular emphasis on its role within the Cajal body.